Cheatgrass (Bromus tectorum L.) interactions with arbuscular mycorrhizal fungi in the North American steppe: prevalence and diversity of associations, and divergence from native vegetation - Busby, Ryan Ray, author; Paschke, Mark, advisor; Beck, George, committee member; Gebhart, Dick, committee member; Meiman, Paul, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: big sagebrush; plant-soil feedbacks; plant-microbe interactions; cheatgrass; ecological restoration; arbuscular mycorrhizal fungi